Assembly of the Escherichia coli 30S ribosomal subunit reveals protein-dependent folding of the 16S rRNA domains. - Mandiyan, V (1991)
Protein-nucleic acid interactions involved in the assembly process of the Escherichia coli 30S ribosomal subunit were quantitatively analyzed by high-resolution scanning transmission electron microscopy. The in vitro reconstituted ribonucleoprotein (core) particles were characterized by their morphology, mass, and radii of gyration. During the assembly of the 30S subunit, the 16S rRNA underwent significant conformational changes that were governed by the cooperative interactions of the ribosomal proteins. The sequential association of the first 12 proteins with the 16S rRNA resulted in the formation of core particles containing up to three mass centers at distinct stages of the assembly process. These globular mass centers may correspond to the three major domains (5', central, and 3') of the 16S rRNA. Through the subsequent interactions of the late assembly proteins with the 16S rRNA, two of the three domains merge, yielding the basic structural traits of the native 30S subunit. The fine morphological features of the native 30S subunit became distinctly resolved only after the addition of the full complement of proteins. The fully reconstituted 30S subunits are active in polyphenylalanine synthesis assays. Visualization of the assembly mechanism of the E. coli 30S ribosomal subunit revealed domain-specific folding of the 16S rRNA through the formation of distinct intermediate core particles hitherto not observed.